Inverse dynamics and robust sliding mode control of a planar parallel (2-PRP and 1-PPR) robot augmented with a nonlinear disturbance observer. (October 2015) - Singh, Yogesh; Santhakumar, M.
Abstract: This paper proposes a modular lightweight three degrees of freedom (DOF) vertical planar parallel robotic manipulator with a singularity free working region and that which is partially decoupled. It also addresses the inverse dynamics of the proposed manipulator supported by a robust sliding mode control along with an active disturbance compensation which has been improvised for the proposed vertical planar parallel robotic manipulator in the presence of parameter uncertainties and external disturbances. Disturbance vector comprising of disturbances due to the system dynamic variations namely payload and parameter variations, frictional effects and other additional (unmodelled) effects have been estimated and compensated through the disturbance observer. To demonstrate the effectiveness of the proposed controller, simulations and experiments with a desired characteristic trajectory are performed and, the proposed controller performances have been compared with traditional controllers and recent developed controllers to illustrate the usefulness and efficacy of the proposed controller. Graphical abstract: Highlights: A lightweight and low cost 3-DOF vertical planar parallel robot is proposed. Inverse dynamics of the 3-DOF planar parallel robot (2PRP-PPR) is presented. A robust motion controller with disturbance compensation has been introduced. The proposed controller is validated with prototype experiments. A comparative study of recent advanced motion controllers has been performed.